Volatile Constituents of the Essential Oils from Aerial Parts of Three Ocimum spp - Pisutthanan, Sirintorn; Pisutthanan, Nisit (Asian Health, Science and Technology Reports, 2007)
Three species of Ocimum spp. including 0. tenuiflorum L., 0. basilicum L. and 0. americanum L. were investigated for their volatile constituents. Aerial parts of each specie were collected from Phitsanulok, Thailand and their essential oils were obtained by hydrodistillation. The chemical composition of the essential oil was analyzed by means of gas chromatography-mass spectrometry using standard n-alkane mixtures as internal standards. The major components of 0. tenuiflorum were methyl eugenol (76.3%), beta-caryophyllene (9.9%), germacrene D (3.9%), germacrene A (3.0%) and bomeol (1.0%). The major components of 0. basilicum were methyl chavicol (89.8%), ( -beta-ocimene (2.1%), 1,8-cineol (1.1%), epi-alpha-cadinol (1.1%) and linalool (1.0%). Finally, the major components of 0. americanum were geranial (40.0%), neral (33.6%), linalool (3.8%), beta-caryophyllene (2.5%),nerol (1.7%), geraniol (1.4%), germacrene D (1.4%) and alpha-humulene (1.1%).